Dampak Citra dan Kualitas Layanan Rumah Sakit terhadap Kepuasan Pasien serta Implikasinya terhadap Loyalitas Pasien di Rumah Sakit Mata Lampung Eye Center - Lestari P.R, Rachmi; Kosasih , Kosasih; Rulia, Rulia; Yuliaty, Farida; Asnar, Etty Sofia Mariati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to evaluate the impact of hospital image and service quality on patient satisfaction and its effect on patient loyalty at Lampung Eye Center Hospital. The approach used in this study is a quantitative method with survey techniques. Data was collected through questionnaires distributed to the hospital's patients. The results reveal that both hospital image and service quality have a positive and significant effect on patient satisfaction, both individually and simultaneously. Furthermore, it was found that patient satisfaction significantly affects patient loyalty. Meanwhile, the direct effect of hospital image on patient loyalty was not significant, whereas service quality has a positive and significant direct effect on patient loyalty. Overall, hospital image, service quality, and patient satisfaction contribute positively to patient loyalty. Therefore, this study recommends that the hospital continues to strengthen its positive image, improve service quality, and prioritize patient satisfaction to ensure sustained loyalty.